(BaTiO3)1‐x + (Co0.5Ni0.5Nb0.06Fe1.94O4)x nanocomposites: Structure, morphology, magnetic and dielectric properties. Issue 11 (11th June 2021) - Slimani, Yassine; Shirsath, Sagar E.; Hannachi, Essia; Almessiere, Munirah A.; Aouna, Moustafa M.; Aldossary, Nouf E.; Yasin, Ghulam; Baykal, Abdulhadi; Ozçelik, Bekir; Ercan, Ismail
Abstract: Two phase‐based nanocomposites consisting of dielectric barium titanate (BaTiO3 or BTO) and magnetic spinel ferrite Co0.5 Ni0.5 Nb0.06 Fe1.94 O4 (CNNFO) have been synthesized through solid state route. Series of (BaTiO3 )1‐ x + (Co0.5 Ni0.5 Nb0.06 Fe1.94 O4 ) x nanocomposites with x content of 0.00, 0.25, 0.50, 0.75, and 1.00 were considered. The structure has been examined via X‐rays diffraction (XRD) and indicated the occurrence of both perovskite BTO and spinel CNNFO phases in various nanocomposites. A phase transition from tetragonal BTO structure to cubic structure occurs with inclusion of CNNFO phase. The average crystallites size of BTO phase decreases, whereas that for the CNNFO phase increases with increasing x in various nanocomposites. The morphological observations revealed that the porosity is highly reduced, and the connectivity between grains is enhanced with increasing x content. The optical properties have been investigated by UV−vis diffuse reflectance spectroscopy. The deduced band gap energy ( Eg ) value is found to reduce with increasing the content of spinel ferrite phase. The magnetic as well as the dielectric properties were also investigated. The analysis showed that CNNFO ferrite phase greatly affects the magnetic properties and dielectric response of BTO material. The obtained findings can be useful to enhance the performances of magneto‐dielectric composite‐based systems. Abstract : Nanocomposites of (BaTiO3 )1‐ x + (Co0.5 Ni0.5 Nb0.06 Fe1.94 O4 ) x have been synthesized through solid state route. The structure, morphology, optical, magnetic, and dielectric properties have been investigated. The obtained findings are useful to enhance the performances of magneto‐dielectric composite‐based systems.